IMPACT OF TYPOGRAPHY ON THE VISUAL COMMUNICATION OF A BOOK: APPROACH OF BOOK DESIGNERS - BAKUTYTĖ, JUSTINA (Knygotyra, 2013)
The rapid technological growth of the past few decades has introduced dramatic changes in publishing technology, accompanied by an ever-increasing access to that technology. Publishing has largely moved from the print shop to desktop. With more people having to deal with publication design (whether in MS Word or in professional design software), general knowledge of typography has become more significant in their work. In addition, typography has been facing new challenges as “page media” (books, magazines etc.) are becoming increasingly visual in order to serve the needs of a visually mediated society. These changes caused the emergence of new approaches dealing with typography as a visual medium. The object of this article is the impact of typography on the visual communication of a book. The theoretical part describes the history of typography and visual communication theories. The analysis showed that typographic elements can carry symbolic meanings and for this reason, typography has to be analyzed in the fields of semiotics and medium theory. Conducted qualitative research was designated to determine the predominant viewpoint amongst Lithuanian book designers on the topic. The following conclusions have been drawn: typography has a strong pictorial potential, various typefaces (or fonts) carry different connotations and have diverse influences on the readability, assimilation, interpretation, and impact of the words and concepts they represent. Thus, if a document is a perceptual object, readers actively make judgments as they look at the page. Their perceptions of that page and its typeface(s) are determined in part by their prior experiences and by the associations connected with those experiences. It follows logically that readers could ascribe persona to both the typeface and the text itself based on these perceptions and associations. Additionally, it has been observed that Lithuanian book designers use such techniques in their works. Nevertheless, Lithuania has not developed a strong typographic culture yet due to the lack of typographic traditions and theoretical works regarding this field. This article can be useful for publishing houses and their book designers, students and teachers of book graphics, book design and typography. Based on the theoretical and empirical material collected in this work, further researches can be made analyzing typographic culture in Lithuania.